Diversidade genética de Salminus brasiliensis utilizados em programas de repovoamento - Gomes, Patrícia Cristina (2010)
In recent years there has been a decline in the capture of "dourado" fish (Salminus brasiliensis) in the Paranapanema River. The major factors causing this decline are: clearing of riverside vegetation, excessive fishing effort, capture of young individuals, drainage ponds, regulation of hydrological regime of rivers, construction of dams, pollution and introduction of exotic species. To preserve the genetic diversity of this species, it is necessary to develop programs that can mitigate the impact of dams on spawning. The production of juveniles is an alternative to conservation, aiming to populate fish ponds, large lakes, rivers and dams. But for an effective implementation of repopulation programs it is required genetic monitoring, evaluation of reproductive procedures and scientific support of different areas. The aim of this study was to determine whether there is transposition of individuals of S. brasiliensis on the transposition stairs of the hydroelectric plant of Canoas I and evaluate the genetic diversity of these individuals to renew the stocks of "dourado" at the Station of Hydrology and Aquaculture of Salto Grande and also assess the genetic diversity of breeders (5♂ and 5♀) from the progeny of this mating, which will be used in repopulation programs of the Paranapanema River through the molecular marker RAPD (Random Amplified Polymorphic DNA). The results showed that the transposition stairs of Canoas I allow the transposition of "dourado" (S. brasiliensis) at the middle Paranapanema River and that the three populations collected there can be used to renew the stock of "dourado" at Salto Grande (SP). It was also shown that there was a dominance of only one mating pair of Salminus brasiliensis in the semi-natural reproductive system. However, the genetic variability of the offspring produced by this system was maintained.